Management : an approach to customer expectations - Allen, Gemmy S.; Plunkett, Warren R.; Attner, Raymond F. (Australia : Cengage Learning, 2013)
This tenth edition of management : an approach to customer expectations is a comprehensive survey of the functions of management as they are currently being applied in the United States and around the world.
Fundamentals of management -- Planning for growth -- Creating effective organizations -- Staffing for high performance -- Influencing behavior and actions -- Controlling operations
Includes bibliographical references and index.
Keywords: MANAGEMENT -- TEXTBOOK; BUSINESS -- TEXTBOOK